KESEHATAN BANK BUMN YANG TERDAFTAR DI BEI SEBELUM DAN SELAMA PANDEMI COVID-19 - agung dinarjito; Aris Priatna (PT Wim Solusi Prima, 2021)
This study aims to determine the health condition of State-Owned Enterprises (SOEs) in the banking sector before and during the COVID-19 pandemic. The author uses data on the financial statements of all state-owned banks for the 2017-2020 period. This study is included in a quantitative descriptive study to assess the health of state-owned enterprises in the banking sector listed on the Indonesia Stock Exchange. The data were analyzed using the RGEC model which measures aspects of risk profile, corporate governance, profitability and capital adequacy. The results of the study concluded that after assessing all aspects of RGEC, it was concluded that state-owned banks were in very healthy condition except for Bank BNI and Bank BTN in healthy condition. BNI Bank which seems to have been affected by the Covid-19 pandemic. This is because the health level of BNI Bank in 2017-2019 is categorized as very healthy, but in 2020 it is categorized as healthy. Penelitian ini bertujuan untuk mengetahui kondisi kesehatan Badan Usaha Milik Negara (BUMN) sektor perbankan sebelum dan selama pandemi covid-19. Penulis menggunakan data laporan keuangan semua bank BUMN periode 2017-2020. Penelitian ini termasuk dalam penelitian deskriptif kuantitatif untuk menilai kesehatan BUMN sektor perbankan yang terdaftar di Bursa Efek Indonesia. Data dianalisis menggunakan model RGEC yang mengukur aspek profil risiko, tata kelola perusahaan, profitabilitas dan kecukupan modal. Hasil penelitian menyimpulkan bahwa setelah menilai semua aspek RGEC, disimpulkan Bank BUMN dalam kondisi sangat sehat kecuali Bank BNI dan Bank BTN dalam kondisi sehat. Bank BNI yang terlihat terdampak pandemi Covid-19. Hal ini dikarenakan tingkat kesehatan Bank BNI pada tahun 2017-2019 dikategorikan.